Repurposing Cilostazol for Raynaud's Phenomenon - El-Hachem, Nehme; Fardoun, Manal M.; Slika, Hasan; Baydoun, Elias; Eid, Ali H. (Current Medicinal Chemistry, 2021)
Raynaud's Phenomenon (RP) results from exaggerated cold-induced vasoconstriction. RP patients suffer from vasospastic attacks and compromised digital blood perfusion leading to a triple color change at the level the fingers. Severe RP may cause ulcers and threaten tissue viability. Many drugs have been used to alleviate the symptoms of RP. These include calcium-channel blockers, cGMP-specific phosphodiesterase type 5 inhibitors, prostacyclin analogs, and angiotensin receptor blockers. Despite their variety, these drugs do not treat RP but rather alleviate its symptoms. To date, no drug for RP has been yet approved by the U.S Food and Drugs Administration. Cilostazol is a selective inhibitor of phosphodiesterase-III, originally prescribed to treat intermittent claudication. Owing to its antiplatelet and vasodilating properties, cilostazol is being repurposed as a potential drug for RP. This review focuses on the different lines of action of cilostazol serving to enhance blood perfusion in RP patients.
Keywords: Raynaud' s phenomenon